Pengaruh Penggunaan Media Pengembangan Peluru Terhadap Kemampuan Tolak Peluru Gaya Spin Di MI Al Madinah Balong Ponorogo Tahun Pelajaran 2024-2025 - Nugraha Murdiansyah, Bayu (Shofanah Media Berkah, 2024)
Bullet development media is a media bullet developed by hendra ( 2014) made of plastic balls filled with second aid rubber and then wrapped in nylon cloth and covered with jean cloth so that it has a weight of 500g in diameter of 10.5 centimeters..It's useful to help the trainees in the process of learning bullet resistance..This research was used to determine if there was a media effect on the use of bullet development on spin-style bullet resistance and to know how much the use of a media development of bullets can affect spin-style bullet resistance. This is a research experiment with capital one group pre-experimental design with a design pretest-posttest design and provide treatment to know the effects of media use results of bullets with the total sample 16 students.Data is collected from pretest and posttest conducted in students the medina class 5 mi balong ponorogo.The analysis of the data suggests that the normality pretest 0,065 & gt; 0,05 and post-test 0,067; 0,05 & gt.The value of homogeneity ( sig p. ) 0,074 & gt; 0,05 and results show that the t t 11,784; t16 2,145 & gt, and the sig.0,000; 0,05 & it.The research shows that the second set berdistribusi normal and homogeneous.The results show that that the t ha accepted or process of treatment impact significantly by 26,17 %. With the result, the treatment using media development bullets exert influence over the capacity dismisses bullets style spin class 5 mi balong ponorogo the medina.And impact of 26,17 % than prior to treatment. Given the importance of physical education as a means to improve skill and learning spirit, then the related party is expected to provide more facilities in order to support the training activity of physical physical health exercise (counselers) at teaching activities.